Factores etiológicos de las maloclusiones en pacientes que acuden a tratamiento en la Clínica Integral del Niño - Orellana M., Oriel (2001)
This study recognized the possible etiological factors of malocclusions in children treated at the Orthodontic department of the Universidad Nacional Mayor de San marcos. Lims - Perú. 50 patients where taken at ramdom presenting Class I or Class II skelletal malocclusion 29 male and 21 female. The etiological factors with greater prevalence where the herital factor 30%, big teeth 20% thumb suck 14% bucal respiratory factor 12%